Dimensions of the construct of Islamic financial inclusion for students at the University of Darussalam Gontor, Indonesia - rafid nopram; Atika Rukminastiti Masrifah (NUsantara Islamic Economic Journal, 2023)
Access to finance has an important role in improving people's standard of living and welfare. One of the factors causing the low interest in access to various banking institutions, products, and services is the lack of financial education among Indonesian people. Education is an important point for increasing financial literacy and inclusion. Good education is carried out at productive ages (15-64 years). For this reason, the management of integrated financial access is something that must receive special attention. In this study, researcher took objects at Darussalam Gontor University by taking UNIDA student respondents from each faculty using a random sampling technique with Structural Equation Modeling (SEM) testing on Lisrel 8.8 software. By using financial literacy (financial knowledge, financial behavior, and financial attitudes) and the level of religiosity as exogenous latent variables on the level of Islamic financial inclusion of UNIDA students as endogenous latent variables. The results show that there is a very significant and positive relationship between exogenous latent variables and endogenous latent variables. So it can be interpreted that someone who has a good level of literacy and also a good level of religiosity, has a better level of access to financial services.